Kinematic analysis of Sipa sa Mangis exploring the science of the art - Noh, Yong Goh (Journal of Health Research and Society, 2018)
The purpose of this study is to give a baseline information on the kinematic study of kicking, Sipa sa Mangis, and to determine what muscle activities are involved during that motion. Sipa sa Mangis is one of the traditional sports of Muslim people in Mindanao. Inside kick is primary skill used in this sport. This study was conducted at Sport Biomechanics Laboratory Facility of Korea Institute of Sport Science, Seoul South Korea. To analyze the motion, Nineteen (19) High definition infrared motion cameras (Qualisys Oqus 701+19) were placed with the Ground Reaction Force Plate at the center of a captured volume of a 3m x 4m x2m. (Kistler Type 9281B11). The coordination was calibrated using an L-frame and T-wand for 60 seconds at a sampling rate of 120 frames /sec. Each camera was synchronized using data cables while one master camera delivered the data to the main frame via a LAN cable. The data was analyzed and processed through Qualisys Tract Manager. To determine the muscle activities while kicking, the surface Electromyography (EMG) fitted electrodes were placed at the 12 motor points the leg muscles. All the three sets of data were analyzed using RMS and FIR frequency filters. The initial and termination portion of the signals were ignored for analysis to avoid any noise creeping in. The sampling rate is 1500Hz where RMS filter was calibrated at 50ms and FIR filters at 80-250Hz. Result of the study is revealed through EMG analysis; the Right Tibia Anterior and Right Gastrocnemius muscles were highly activated throughout the different phases of kicking motion.